Dead Boy Detectives by Toby Litt & Mark Buckingham - Litt, Toby, 1968- (DC Comics, 2023)
"Edwin Paine and Charles Roland have a lot in common - they're both English schoolboys who love a good detective story, and they've been known to dabble in mystery-solving themselves. They're also both dead, a condition which has proven to be less of a hindrance than one might think. From the pages of THE SANDMAN, Neil Gaiman's intrepid dead schoolboys head back to the horror that is St. Hilarions School; the place where they both were murdered."--